Positive attributes of anti-TERT CD4 T-helper type 1 immune responses in melanoma - Nagore, Eduardo; Viros, Amaya; Kumar, Rajiv (The journal of investigative dermatology, 2022)
Nardin et al's (2021) study on melanoma reports anti-TERT CD4 T helper type (Th) 1 responses in more than half of patients. Besides indicating a trend for improved survival, increased anti-TERT CD4 Th1 responses predicted better outcomes for patients treated with immune checkpoint inhibitors. Thus, harnessing systemic anti-TERT CD4 Th1 responses together with tumor-specific elevation of telomerase can potentially open new avenues for biomarkers and treatment in melanoma.